Fiqh muamalat case study: usury riba in financial system in Malaysia / Nihayah Ibrahim … [et al.] - Ibrahim, Nihayah; Mohd Masri, Siti Nur Nadhiraathira; Kamarudin, Nur Halimatus Saadiyah; Mahadir, Siti Ainin Sofiya (2023)
Riba known as interest or usury is fundamentally prohibited both by the Qur'an and the Sunnah. On the concept of interest, there is no doubt or dispute among Muslims that it is absolutely prohibited. In a modem economy in which interest is a fundamental part, this can lead to a necessary change of objectives and perspectives when working within the framework of lslamic economics. One of the main issues of prohibiting interest is that interest rates are used to regulate demand in modern finance. A particular interest rate is equivalent to a price for a particular investment. With no interest, credit becomes impossible to handle under traditional capitalist models. Islamic economists propose replacing interest rates with profit sharing, selling goods for their cost, or even leasing. All of these alternatives would necessarily make certain speculative practices and artificial interest rate manipulation practices obsolete. However, Islamic economists agree that this would actually be a good thing. One possible alternative consists in the creditor acting as a partner in a contract between an investor and an entrepreneur. Basically, in Islamic economics banks must be able to generate returns through investments in productive projects rather than relying solely on interest rates.